2019
DOI: 10.17221/23/2019-jfs
|View full text |Cite
|
Sign up to set email alerts
|

Distance driven and driving speed when forwarding during final felling in Central Sweden

Abstract: Factors affecting forwarding work are interesting because they can be used to better optimize forwarding routes and to predict costs. The main objective of this study was to investigate the association between driving speed and driving distance when forwarding. Data was automatically collected during 2.5 years from two large forwarders operating during final felling in central Sweden. Driving speeds for the work tasks Driving unloaded, Loading drive and Driving loaded were analysed using correlation, least-squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
2
14
0
Order By: Relevance
“…We found that productivity and TTD were strongly correlated. These results are consistent with many published studies, such as Matthews et al, [48], Kumazawa et al, [49], and Berg et al, [50]. These studies posited that the driving unloading speed increases with an increase in driving distance.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that productivity and TTD were strongly correlated. These results are consistent with many published studies, such as Matthews et al, [48], Kumazawa et al, [49], and Berg et al, [50]. These studies posited that the driving unloading speed increases with an increase in driving distance.…”
Section: Discussionsupporting
confidence: 93%
“…In addition, extraction productivity may be influenced by the number of logs [46,50]. This pattern could be explained by the fact that productivity increases with a decrease in the number of load stops and driven distances.…”
Section: Discussionmentioning
confidence: 99%
“…Speed is suggested to increase during stress to maintain high productivity, e.g. during long distances (Berg et al 2019). High productivity demands in rough terrain may therefore cause high postural loads and may be something to consider when setting productivity norms, so the operational productivity goals are balanced to the operators' risk for occupational health problems.…”
Section: Discussionmentioning
confidence: 99%
“…However, no systematic rule-based filtering was used to remove outliers (cf. Berg et al 2019). In general, beyond specifying which boom-control system was used, the data-gathering did not require any special arrangements or changes to working practices.…”
Section: Randomized Follow-upmentioning
confidence: 99%